Chemokines play complex roles in cerebral ischemia. (January 2018) - Chen, Chen; Chu, Shi-Feng; Liu, Dan-Dan; Zhang, Zhao; Kong, Ling-Lei; Zhou, Xin; Chen, Nai-Hong
Abstract: Ischemic stroke (IS) is a disease caused by deficiency of blood and oxygen in focal or complete brain, followed by inflammation cascade and other pathological reactions, which finally lead to irreversible damage to the cerebrum. For the inflammation is a key progress at the initiation of ischemia and poststroke, and chemokines work as vital cytokines in inflammation, we focus the roles of chemokines in IS. Studies have shown cerebral ischemia is associated with marked induction of both CXC and CC chemokines which resulting in extensive leukocyte infiltration in the ischemic brain, and neutrophil infiltration may increase cerebral edema inducing injury in the ischemic area. In addition, chemokines also shows other functions such as promote neuroblast migration, hematogenous cell recruitment and functional brain repair. Thus, a similar chemokine ligand/chemokine receptor pair can mediate both beneficial and detrimental effects depending on the window of observation and pathophysiological conditions. This manuscript reviews the studies about chemokine-mediated effects in cerebral ischemia/reperfusion and discusses the potential significance of these interactions in injury and repair of ischemic tissues. We also refer drug development based on the chemokines and clinical applications using chemokines as diagnostic or prognostic biomarkers in ischemic stroke. Highlights: Chemokines play complex roles via constitutive expression and induced inflammatory expression in cerebral ischemia setting. Chemokines can show both beneficial and detrimental function at the initiation of stroke and poststroke. Drugs designed based on chemokines need further study. Chemokines may become biomarkers for diagnostic and prognostic for ischemic stroke.